The Use of Simplified Debate to Teach Speaking in English Extracuricullar Class (EEC) in SMAN 1 BABAT (RETAIN, 2013)
This study investigated about the technique that was used by the English teacher to teach speaking in English Extracurricular Class (EEC). It was aim to answer the following questions: How does the teacher apply Simplified Debate to teach speaking in English Extracurricular Class (EEC) in SMAN1 BABAT? What do the students learn when simplified debate is used? This study was limited to both the teacher and the students of EEC. So, qualitative case study was used in this research. The data were taken from the results of fieldnotes, semi-structured interview, and questionnaire. The data that were gotten were analyzed qualitatively. It was found that the implementation of Simplified Debate technique was done based on the Lustigova’s (2011) procedure, although the teacher missed some steps and also was modified by the teacher. From the implementation of Simplified Debate the students learned to speak in public, to speak fast, to create their own words, this technique could encourage the students to be active in the class.Key words: Speaking, debate, technique, English extracurricular class (EEC) AbstrakPenelitian ini menginvestigasi tentang jenis technique mengajar yang digunakan oleh guru untuk mengajar speaking ekstrakurikuler bahasa inggris. penelitian Ini di gunakan untuk mencari jawaban dari pertanyaan yang ada: Bagaimana guru menerapkan Simplified debate untuk mengajar speaking di ekstrakurikuler bahasa inggris di SMAN 1 BABAT? Apa yang murid-murid bisa pealjari ketika teknik ini di gunakan? Penelitian ini dibatasi pada guru dan murid dari EEC. Jadi qualitative case study adalah metode yang digunakan dalam penelitian ini. Data diambil dari hasil fieldnotes, interview semi-structured, dan questionnaire. Data yang didapat dianalisa secara kualitatif. Ditemukan bahwa penerapan teknik Simplified Debate ini di lakukan sesuai dengan procedure dari Lustigova (2011). Meskipun dalam penerapan ini guru tidak melaksanakan beberapa tahap dan juga karena tahap tahapanya sudah di modifikasi oleh guru. Dari penerapn teknik ini murid-murid belajar untuk berbicara di depan umum, untuk berbicara cepat, untuk merangkai kata mereka sendiri, teknik ini bisa mendorong murid-murid untuk aktif di dalam kelas.Kata-kata Kunci: speaking, debat, teknik, ekstrakurikuler bahasa inggris.